Effect of incorporation of detoxified karanja (Pongamia pinnata) and neem (Azadirachta indica) seed cakes in total mixed rations on milk yield, composition and efficiency in crossbred dairy cows - RAJ, D N; RAMANA, J V; RAO, S B N; KUMAR, D DINESH; SURYANARAYANA, M V A N; REDDY, Y RAVINDRA; PRASAD, K S (The Indian Journal of Animal Sciences, 2016)
In the present study, neem seed cake (51.55% CP) and karanja seed cake (37.91% CP) were used as a partial replacement of soybean protein cake. Three iso-nitrogenous total mixed rations (TMR) were prepared namely T1-control where soybean meal was incorporated at 9.6% of TMR, in T -dNC and T -dKC, the cakes were incorporated at 3.85 and 5.85% of TMR and fed to eighteen crossbred cows in three groups for 90 days. Milk yield (kg/day) and FCM yield (kg/day) was found to be higher in dNC compared to dKC groups. After 90 days of feeding, both milk yield (kg/ day) and FCM yield (kg/day) increased in all the groups. The average milk fat was found to be lower in (P<0.05) in T3-dKC group (5.03) compared to T1-control (6.13). Total solids was found to be lower in T2-dNC and T3-dKC groups compared to T1 control. DMI (kg) required for kg FCM was same in all the groups (1.38 in T1-control; 1.30 in T2- dNC and 1.66 in T3-dKC). It was concluded that detoxified neem cake (dNC) and detoxified karanja cake (dKC) can be included in total mixed rations of medium producing dairy cattle (5–8 liters of milk per day) replacing standard soybean meal without adversely affecting milk composition and milk production efficiency.